Adaptation of a Mice Doppler Echocardiography Platform to Measure Cardiac Flow Velocities for Embryonic Chicken and Adult Zebrafish - Benslimane, Fatiha M.; Alser, Maha; Zakaria, Zain Z.; Sharma, Anju; Abdelrahman, Hana A.; Yalcin, Huseyin C. (Frontiers in Bioengineering and Biotechnology, 2019)
Ultrasonography is the most widely used imaging technique in cardiovascular medicine. In this technique, a piezoelectric crystal produces, sends and receives high frequency ultrasound waves to the body to create an image of internal organs. It enables practical real time visualization in a non-invasive manner, making the modality especially useful to image dynamic cardiac structures. In the last few decades, echocardiography has been applied to in vivo cardiac disease models, mainly to rodents. While clinical echocardiography platforms can be used for relatively large animals such as pigs and rats, specialized systems are needed for smaller species. Theoretically, as the size of the imaged sample decreases, the frequency of the ultrasound transducer needed to image the sample increases. There are multiple modes of echocardiography imaging. In Doppler mode, erythrocytes blood flow velocities are measured from the frequency shift of the sent ultrasound waves compared to received echoes. Recorded data are then used to calculate cardiac function parameters such as cardiac output, as well as the hemodynamic shear stress levels in the heart and blood vessels. The multi-mode (i.e. b-mode, m-mode, Pulsed Doppler, Tissue Doppler etc.) small animal ultrasound systems in the market can be used for most in vivo cardiac disease models including mice, embryonic chick and zebrafish. These systems are also associated with significant costs. Alternatively, there are more economical single-mode echocardiography platforms. However, these are originally built for mice studies and they need to be tested and evaluated for smaller experimental models. We recently adapted a mice Doppler echocardiography system to measure cardiac flow velocities for adult zebrafish and embryonic chicken. We successfully assessed cardiac function and hemodynamic shear stress for normal as well as for diseased embryonic chicken and zebrafish. In this paper, we will present our detailed protocols for Doppler flow measurements and further cardiac function analysis on these models using the setup. The protocols will involve detailed steps for animal stabilization, probe orientation for specific measurements, data acquisition, and data analysis. We believe this information will help cardiac researchers to establish similar echocardiography platforms in their labs in a practical and economical manner.